2000
DOI: 10.1002/we.33
|View full text |Cite
|
Sign up to set email alerts
|

Using Wavelet Analysis to Assess Turbulence/Rotor Interactions

Abstract: Large loading events on wind turbine rotor blades are often associated with transient bursts of coherent turbulent energy in the turbine inflow. These coherent turbulent structures are identified as peaks in the three-dimensional, instantaneous, turbulent shearing stress field. Such organized inflow structures and the accompanying rotor aeroelastic responses typically have timescales of only a few seconds and therefore do not lend themselves to analysis by conventional Fourier spectral techniques. Wavelet anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 1 publication
0
38
0
Order By: Relevance
“…These coherent structures are produced by strong shearing from nocturnal low-level jets and can be damaging to turbine rotor components (Kelley et al 2001, Hand et al 2003. The wind farm studied here does not appear to experience strong "topdowned" turbulence on stable nights as low-level jets are very infrequent.…”
mentioning
confidence: 85%
“…These coherent structures are produced by strong shearing from nocturnal low-level jets and can be damaging to turbine rotor components (Kelley et al 2001, Hand et al 2003. The wind farm studied here does not appear to experience strong "topdowned" turbulence on stable nights as low-level jets are very infrequent.…”
mentioning
confidence: 85%
“…As has been discussed by Kelley [10], time-frequency analysis using continuous wavelet transforms can help study energetic peaks that occur coincidentally with higher-order modes that might not be detected through spectral analysis. Wavelet analysis of the loads data was performed to determine whether cutting off high frequencies in the inflow turbulence would affect turbine load characteristics in any significant way.…”
Section: Wavelet Analyses Of Turbine Loadsmentioning
confidence: 99%
“…Wavelet analysis of the loads data was performed to determine whether cutting off high frequencies in the inflow turbulence would affect turbine load characteristics in any significant way. Also, non-stationary characteristics of loads from aeroelastic simulations such as flapwise bending loads that can change based on azimuthal position of blades may be lost by relying only on spectral analysis [10]; then, wavelet analysis can again be useful. Figure 3(a,c,e) summarizes results of the wavelet analysis for the FBM process resulting from an unfiltered inflow (13 × 13 grid and 32 Hz sampling) and an inflow filtered at 1 Hz on a 9 × 9 grid (for a hub-height mean wind speed of 12 m/s).…”
Section: Wavelet Analyses Of Turbine Loadsmentioning
confidence: 99%
“…b In addition, u * has been shown to be a good indicator of the number of high-loading events on a turbine 14,15 and may therefore be a useful value for analyzing the performance of a controller based on wind preview measurements. Results of RMS errors between true and b While the GP LLJ spectra scale with u * , other spectral models such as the IEC models scale with σu.…”
Section: B Impact Of Turbulence On Measurement Errorsmentioning
confidence: 99%
“…Analysis of measurements of coherent structures, such as Kelvin-Helmholtz billows, in the wind fields is needed. Studies have shown that coherent structures cause severe turbine loads, 14 and it is a goal of wind preview based controllers to mitigate the loads caused by coherent structures. Therefore, it is essential to determine the fidelity that LIDAR measurements of coherent structures can achieve.…”
mentioning
confidence: 99%